2006
DOI: 10.1021/jp065507w
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Chemical Shifts and Quadrupole Couplings for Different Hydrogen-Bonding Cases Occurring in Liquid Water:  A Computational Study

Abstract: Nuclear magnetic resonance (NMR) parameters are determined theoretically for the oxygen and hydrogen/deuterium nuclei of differently hydrogen-bonded water molecules in liquid water at 300 K. The parameters are the chemical shift, the shielding anisotropy, the asymmetry parameter of shielding, the nuclear quadrupole coupling constant, and the asymmetry parameter of the nuclear quadrupole coupling. We sample instantaneous configurations from a Car-Parrinello molecular dynamics simulation and feed nuclear coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…The only computationally efficient way to compute spectroscopic parameters for complex liquids using hybrid and meta‐GGA functionals consists of extracting trajectory snapshots from a Car–Parrinello molecular dynamics simulation and feeding them into a separate quantum chemistry package. This has been done by the Vaara group for liquid water 37, 38. Their results show that this method has the potential to be very accurate, but it requires the combination of two distinct codes.…”
Section: Introductionmentioning
confidence: 99%
“…The only computationally efficient way to compute spectroscopic parameters for complex liquids using hybrid and meta‐GGA functionals consists of extracting trajectory snapshots from a Car–Parrinello molecular dynamics simulation and feeding them into a separate quantum chemistry package. This has been done by the Vaara group for liquid water 37, 38. Their results show that this method has the potential to be very accurate, but it requires the combination of two distinct codes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the question of whether NMR properties can be predicted at all in static structures (such as those typically dealt with in computational chemistry) is emerging as a novel area of investigation 38. Indeed, it has been shown that in many cases, success can be attained only by going beyond static molecules,3942 that is, dealing not only with the species of interest, but with the environment and its dynamics as well.…”
Section: Introductionmentioning
confidence: 99%
“…1 H chemical shifts are sensitive to the number of hydrogen bonds and the structure of the developed hydrogenbonded network of H2O molecules. 42 Also, to geometrical constraints and confinement effects at the material surface. 43 To shed light on the chemical nature of protons contributing to the 1 H NMR signals in the 0-2.1 ppm region, chemical shifts histograms resulting from our MD-DFT/GIPAW calculations obtained for the four scenarios of adsorbed water molecules and hydroxyl groups have been prepared.…”
Section: Anatase (101)mentioning
confidence: 99%